PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH KOPERASI SIMPAN PINJAM KARYA UTAMA MANDIRI (KSP KARUMA) KOTA SEMARANG - David Saputro, 11.05.51.0116 (Students Journal of Economic and Management, 2016)
This research was conducted at KSP Karya Utama Mandiri (KARUMA) Semarang with the aim of research to determine the effect the dimensions of reliability, responsiveness of service, assurance, empathy and physical evidence (tangible) service to satisfaction KSP customers KARUMA Semarang. A sample of 100 respondents, using accidental sampling technique that researchers choose any members of the population who happen to meet with researchers that are considered to provide the necessary information. Methods of data analysis using linear regression. The test results showed that the dimensions of reliability service, responsiveness dimensions or responsiveness, assurance or guarantee the dimension, the dimension and the dimension of empathy or concern tangibles or physical evidence of a positive effect partially and simultaneously toward customer satisfaction KSP KARUMA Semarang.Â Keywords: service quality, reliability, responsiveness, assurance, empathy, tangibles customer satisfaction.